Percepções de professoras sobre as implicações da formação do PNAIC-Matemática em suas práticas - Ana Cristina Gonçalves Carvalho (2018)
In this research, we aim to identify and analyze the teacher's perceptions about the implications of the PNAIC-Mathematics formation. The National Pact for Literacy in the Right Age (PNAIC) was a formal commitment between the Federal Government, States and Municipalities, with the objective of teaching Portuguese and Mathematics to children up to 08 years of age, that is, at the end of the literacy. To this end, the Program envisaged four lines of action: face-to-face training for public school teachers and their teaching supervisors; distribution of materials; systematized evaluation; mobilization and control of those involved in the process. From the point of view of the methodological approach, the present study is in the field of qualitative research. The data collection was done through an electronic questionnaire sent to 350 teachers who attended the PNAIC in Contagem in the year 2014, when the training approached Mathematical Literacy. We obtained 62 responses and conducted interviews with five of these teachers. In order to compose the documentary, we also produced the educational product of this research, recording the practice of four teachers interviewed. We concluded that training programs such as the PNAIC needs to consider the social complexity resulting from the different working conditions that teachers and students face in classrooms such as economic exclusion, violence, lack of infrastructure and didactic resources. In addition to considering social complexity and dialoguing with other public policies, the PNAIC should be articulated with a career plan to enhance the professional development of the teacher. We understand the PNAIC as a formation perceived by the teachers in a positive way, with a rich material, and that has caused changes in the relationship with their students, due to a greater listening in the moment of letting them explain their reasoning, greater approximation and a more ludic work from the games.